INTELLECTUAL PROPERTY RIGHTS’ LEGAL PROTECTION TOWARDS COPYRIGHTS OF NEW CREATION DANCE CHOREOGRAPHY IN LAMPUNG - Darul Kutni Al Muroni (Faculty of Law, Universitas Lampung, 2022)
The copyright law determines that the state holds a copyright owner regarding traditional cultural expressions. What if a cultural expression undergoes renewal and is created into a new dance that still has a traditional theme. The purpose of this study is to describe the form of the legal protection of intellectual property rights as well as constraints in determining who is the legal owner of the copyright of the creation of new dance choreographies in Lampung. The research method used is the socio-legal approach, namely by using an approach that focuses on seeing the law through a combination of normative analysis (juridical legal norms) and non-legal science approaches. The data used are primary data and secondary data using qualitative analysis. The results of this study indicate that legal protection of Intellectual Property Rights based on the Copyright Law of 2014 is preventively provided to prevent an infringement of a copyrighted work, especially new creative dance creations, preventive actions that can be taken to protect dance creations. A new creation is by recording the work as regulated in Articles 66-67 of the Copyright Law. This legal protection is given to find a form of a solution in defending the rights of the creator of the work. The obstacle is a lack of understanding of the importance of copyright registration, the registration procedure and process, which are still considered complicated, and the registration fee, which is still deemed burdensome to artists.